Combined Effect on Antioxidant Properties of Gymnema Sylvestre and Combretum Micranthum Leaf Extracts and the Relationship to Hypoglycemia - A., Ibrahim; E., Onyike; A.J., Nok; I.A., Umar (European Scientific Journal, ESJ, 2017)
Gymnema sylvestre R.Br. (“periploca of the woods” in English; “Kafi suga” in Hausa) (Asclepiadaceae) and Combretum micranthum, Fam. (Géézà in Hausa) (Combretaceae)) are used in combination for the management of diabetes mellitus (DM) in the North-Eastern part of Nigeria with little or no scientific basis. It is thus the aim of this research to validate the anti-diabetic activities of G. sylvestre (GS) and C. micranthum (CM) leaf extracts, individually and in combined form (GSCM) as well as look at the relationship between antioxidant capacity and anti-hyperglycemic potential of these plants. The study assayed for anti-diabetic potential by following fasting blood glucose (FBG). Levels of liver catalase (CAT), malondialdehyde (MDA), superoxide dismutase (SOD), reaction oxygen species (ROS), reduced glutathione (GSH), oxidized glutathione (GSSG) and glutathione peroxidase (GSH-Px), and radical scavenging activities of the plants were assayed for spectrophotometrically. GS and CM revealed good ferric reducing antioxidant power (FRAP) and radical scavenging activities against ABTS, DPPH and Nitric Oxide with C. micranthum being significantly better - both plants also showed good total flavonoids and total phenolic contents. The anti-hyperglycemic activities may be associated with flavonoids and phenolic compounds which act via radical scavenging/antioxidant properties of the plants’ extracts. In conclusion, G. sylvestre and C. micranthum aqueous leaf extracts showed significant (P < 0.05) hypoglycaemic activities both separately and in a 1:1 combination which has strong correlation with both in vitro and in vivo antioxidant activities of the plants’ extracts.